Pengembangan Website pada Gereja Santa Maria de Fatima - Verich Veracious (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
The development of Church of Santa Maria de Fatima’s Website. Because the data displayed on the website is static, making it difficult to update. In other words, there is no information system in the website. The new website was built on PHP (Hypertext Preprocessor) programming language and utilising MySQL as DBMS (Data Base Management System). The method used in the development of this website is Prototyping. Based on the experiments that have been done, it can be concluded that the website has been made more dynamic. Thus, the data displayed on the website can be more easily updated and helps the management of the website